CURRENT SITUATIONS IN THE CHRISTIAN CONTEXT FROM THE ASPECT OF THE GENDER PERSPECTIVE (Religious dialogue and cooperation, 2025)
This study aims to analyze three key dimensions: the historical-cultural approach, theologicalinterpretations, sociological analyses, and narratives, with a particular emphasis on theOld Testament and gender asymmetry in the creation myth, as well as the Apostle Paul’s teachingson women. The historical-cultural approach seeks to investigate the historical foundations of genderroles within Christianity and the various interpretations that have shaped societal attitudesand norms concerning gender. Additionally, this research will examine the manifestations of genderwithin Christian communities, particularly the status of women in the Christian tradition andthe role of Christianity in shaping and reinforcing gender stereotypes. This involves an explorationof gender dynamics across different Christian denominations, highlighting both progressive andconservative perspectives. Furthermore, this study will address women’s activism and the role offeminist theology, commonly referred to as Christian feminism, within Christian communities. Itwill examine contemporary challenges faced by women in their efforts to resist patriarchal traditionsand explore potential avenues for transforming patriarchal structures within religious institutions.Ultimately, this research aims to assess the broader impact of the Christian tradition onmodern society and its influence on religious and cultural frameworks from a gendered perspective.
Keywords: Gender; Christianity; Women’s rights; Feminism; Patriarchy